How to Improve the Independent Ability of ForCES Routers - Qi Fang; Weiming Wang; Xiaochun Wu (Institute of Advanced Engineering and Science, 2013)
As network requirement of a new generation emerges, such as the endless stream of multimedia services and data center network, network management is heavy, extremely difficult and prone to error. How to achieve the self-management of the network, reduce manual input and improve stability and high efficiency of network is a hot topic in the field of network technology. As we known, network element needs to support the capability of self-management. But in the ForCES architecture, the self-management of network nodes is clearly insufficient. Based on the cognition with the characteristics of artificial intelligence, we explore the ForCES architecture introducing cognizance. So it has the capable of self-learning and self-management. This paper focuses on introducing the basic features, architecture and key technologies of cognition-based ForCES by means of the traditional definition and features of ForCES. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2179